2023
DOI: 10.3390/medicina59030597
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Biomarkers and Scores in Describing Urosepsis

Abstract: Background and Objectives: Patients with urinary tract obstruction (UTO) and systemic inflammatory response syndrome (SIRS) are at risk of developing urosepsis, whose evolution involves increased morbidity, mortality and cost. The aim of this study is to evaluate the ability of already existing scores and biomarkers to diagnose, describe the clinical status, and predict the evolution of patients with complicated urinary tract infection (UTI) and their risk of progressing to urosepsis. Materials and Methods: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…We observed that a lower CRP concentration and the positive outcome of participating patients are in line with that finding. The severity of sepsis was associated with procalcitonin concentrations [ 42 , 44 , 45 , 46 ], and at the same time, procalcitonin can be used as an early predictor of postoperative urosepsis [ 46 ]. Postoperative urosepsis was also associated with urine that tested positive for nitrite, WBC [ 47 ], and leukocyte esterase [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that a lower CRP concentration and the positive outcome of participating patients are in line with that finding. The severity of sepsis was associated with procalcitonin concentrations [ 42 , 44 , 45 , 46 ], and at the same time, procalcitonin can be used as an early predictor of postoperative urosepsis [ 46 ]. Postoperative urosepsis was also associated with urine that tested positive for nitrite, WBC [ 47 ], and leukocyte esterase [ 47 ].…”
Section: Discussionmentioning
confidence: 99%